Respuesta :

Given:

The given polynomial is:

[tex]f(x)=[/tex] [tex]3x^{2}-3x+1[/tex]

To find the roots of the given polynomial.

To find the roots we have to take [tex]f(x) = 0[/tex]

So,

[tex]3x^{2} -3x+1 = 0[/tex]

Formula

By quadratic formula, the root of the equation [tex]ax^{2} +bx+c = 0[/tex] is,

[tex]x = \frac{-b+\sqrt{b^{2}-4ac } }{2a}[/tex] and [tex]\frac{-b-\sqrt{b^{2} -4ac} }{2a}[/tex]

Now,

Putting, [tex]a=3, b=-3, c=1[/tex] we get,

[tex]x = \frac{3+\sqrt{3^{2}-4(3)(1) } }{(2)(3)}[/tex] and [tex]\frac{3-\sqrt{3^{2}-4(3)(1) } }{(2)(3)}[/tex]

[tex]x = \frac{3+\sqrt{-3} }{6}[/tex] and [tex]x=\frac{3-\sqrt{-3} }{6}[/tex]

Hence,

The values of the roots of the given polynomial are[tex]x=\frac{3+\sqrt{-3} }{6}[/tex] and [tex]x=\frac{3-\sqrt{-3} }{6}[/tex]

Hence, Option A and F are the correct answer.

ACCESS MORE